Conservation of Saas forest (Phraisaas) with participation According to the Geo-Cultural landscape principle Thai and Cambodian border communities - Srisombat, Ittiwat; Saluth, Bun (Journal of Local Governance and Innovation, 2019)
The purpose of this research is to study To study participatory forest conservation methods according to the community cultural landscape principles and to study the factors that promote and obstacles in forest conservation (Pa Raya Saad) participatory model based on the principles of cultural landscape, Thai border communities and Cambodia By using participatory action research The group of key informants includes 30 monks, community leaders, local wisdom and people. Tools for data collection Interview and observation Analyze and synthesize data by interpreting and creating conclusions.The researchfound that Cultural landscape for forest conservation with participation in the Thai and Cambodian border communities By monks, villagers, youth, government agencies and private organizations Together in the conservation of forests by taking advantage of the future Settlement history Battle event Faith and religion Public mind and social crisis with the forest and networking with people outside the community, both government and non-government organizations Forest conservation methods Monks are leaders in learning and conserving forests, ordination of forests. Determination of the sanctuary area, digging the ditches around the forest area Dredging creeks and swamps in the forest The forest Entering a forest conservation camp Daily merit making activities Activity for labeling consciousness or talking trees Arranging guard duty for forest protection Destruction of traps, both on land and in swamps Coordinating, requesting assistance, cutting-edge tools and technology from private organizations and public relations through domestic and international mass media Factors that promote forest conservation Monks are the mainstay of the villagers. There are village directors and government agencies supporting as a supporting factor. The obstacle is the lack of villagers who dare to volunteer to be a leader in forest conservation and lack of budget Good practice guidelines Should encourage the whole country to participate in forest conservation clearly To allow the community to realize and cooperate to preserve the forest as a classroom and tourist attraction to study nature